2017
DOI: 10.2217/pgs-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness of the Roma Population within CYP2B6 Worldwide Variation

Abstract: This study provides the first data of several CYP2B6 polymorphisms in Roma population and indicates the need for systematic investigation of the most important pharmacogenes' variants in this large, transnationally isolated population worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Significant genetic differentiation from general Europeans in SNPs in the CYP2C and CYP2D subfamily regions was also found in previous research of isolated populations in Europe (Roma, Basques, and Orcadians) [ 50 ]. Among the former analyses of ADME polymorphisms in Roma populations, Tomas et al [ 27 ] particularly studied 3 SNP loci in the CYP2B6 gene, Spikey et al [ 51 ] studied 4 SNP loci in the MDR1 gene while Nagy et al [ 15 ] analyzed 2 SNP loci in the SLCO1B3 gene and all of them confirmed that the Roma differ considerably from geographically close majority populations, as well as from Indian populations in those particular loci. Such results are not surprising knowing Roma genetic history which is influenced by strict rules of group endogamy, reproductive isolation and specific mating practice and isolation over the past several centuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant genetic differentiation from general Europeans in SNPs in the CYP2C and CYP2D subfamily regions was also found in previous research of isolated populations in Europe (Roma, Basques, and Orcadians) [ 50 ]. Among the former analyses of ADME polymorphisms in Roma populations, Tomas et al [ 27 ] particularly studied 3 SNP loci in the CYP2B6 gene, Spikey et al [ 51 ] studied 4 SNP loci in the MDR1 gene while Nagy et al [ 15 ] analyzed 2 SNP loci in the SLCO1B3 gene and all of them confirmed that the Roma differ considerably from geographically close majority populations, as well as from Indian populations in those particular loci. Such results are not surprising knowing Roma genetic history which is influenced by strict rules of group endogamy, reproductive isolation and specific mating practice and isolation over the past several centuries.…”
Section: Discussionmentioning
confidence: 99%
“…Their pronounced genetic differences from the majority Croatian population and traces of their ancestral origins have been detected in mitochondrial DNA [ 22 ], Y chromosome markers [ 23 , 24 ] and various autosomal common [ 25 ] and rare disease loci [ 26 ]. The recent study of ADME gene's CYP2B6 polymorphisms proved the distinctive position of the Croatian Roma in the world's populational variability [ 27 ] and indicated the need for a systematic investigation of the most important pharmacogenes' variants in the Roma.…”
Section: Introductionmentioning
confidence: 99%
“…This population has the same health status as the older general population in the UK. Ethnicity was described by the interviewer based on appearance and parental origin [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, in Roma, allelic differences in lactate dehydrogenase (Hubácek et al., 2017b), drug metabolism enzymes (Tomas et al., 2017, Dlouhá et al, in press), or osteoprotegerin (Mydlárová Blaščáková et al., 2017) polymorphisms clearly underlie genetic differences that could have important clinical (optimal treatment or dietary recommendations) or live expectancy consequences.…”
Section: Discussionmentioning
confidence: 99%